The Mathematical Connection Ability of Junior High School Student’s Through The Scientific Approach and Guided Inquiry Method - Rifaatul Mahmudah; Fika Muji Fadhillah; Rudy Kurniawan (IKIP Siliwangi, 2019)
This study used the pre-test post-disigned quasi-experimental method. The purpose of this study was to find out the achievement and improvement of mathematical connection ability of students whose learning using the scientific approach and guided inquiry method was better than those using the scientific approach only. This research was conducted at the junior high school level. The instrument used in this study was a test of mathematical connection ability. The results showed that learning using the scientific approach and guided inquiry method was better than those using the scientific approach only in improving students mathematical connection ability, both from the significance of t-test posttest 0.017 and from the results of the t-test n-gain significance of 0.024. For the difficulty of solving the problem of experimental class mathematical connection ability lies in the percentage of questions number 6 which is 46.9% with indicators applying the relationship of mathematics to everyday problems, while the percentage of achievement in the control class is very low in question number 5 is 46.1% with indicators look for the relationship of one procedure to another in equivalent representations. Learning using the scientific approach and guided inquiry method makes creative students associate concepts or mathematical procedures appropriately.